2020
DOI: 10.3390/genes11111307
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Characterization of Incompatibility Group FIB Positive Salmonella enterica Serovar Typhimurium Isolates from Food Animal Sources

Abstract: Salmonella enterica is one of the most common bacterial foodborne pathogens in the United States, causing illnesses that range from self-limiting gastroenteritis to more severe, life threatening invasive disease. Many Salmonella strains contain plasmids that carry virulence, antimicrobial resistance, and/or transfer genes which allow them to adapt to diverse environments, and these can include incompatibility group (Inc) FIB plasmids. This study was undertaken to evaluate the genomic and phenotypic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…On the other hand, all isolates carried an IncFIB plasmid that could increase colonization in the chicken cecum, which may help to explain its persistence in the food animal population [52]. Within the plasmid IncFIB, some of the common resistance genes identified were similar to those previously reported [53], including AAC(3)-IV, aadA2, APH(4)-Ia, cmlA1, dfrA12, floR, sul1, sul3, and tet(A), which encode resistance to gentamicin, streptomycin, hygromycin B, chloramphenicol, trimethoprim, florphenicol, sulfonamides, and tetracycline, respectively. It should be noted that gentamicin is a critically important antimicrobial, while chloramphenicol, trimethoprim, sulfonamides, and tetracycline are highly important antibiotics in human medicine, according to the latest WHO publication [54].…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, all isolates carried an IncFIB plasmid that could increase colonization in the chicken cecum, which may help to explain its persistence in the food animal population [52]. Within the plasmid IncFIB, some of the common resistance genes identified were similar to those previously reported [53], including AAC(3)-IV, aadA2, APH(4)-Ia, cmlA1, dfrA12, floR, sul1, sul3, and tet(A), which encode resistance to gentamicin, streptomycin, hygromycin B, chloramphenicol, trimethoprim, florphenicol, sulfonamides, and tetracycline, respectively. It should be noted that gentamicin is a critically important antimicrobial, while chloramphenicol, trimethoprim, sulfonamides, and tetracycline are highly important antibiotics in human medicine, according to the latest WHO publication [54].…”
Section: Discussionsupporting
confidence: 76%
“… Gygli et al (2019) reported that the possible discrepancy between gene detection by WGS and antibiotic susceptibility testing of Mycobacterium tuberculosis strains could arise because the clinical concentrations established to classify it as resistant have cutoff scores that are too high, thus misclassifying strains as susceptible. Aljahdali et al (2020) , found a positive concordance between the presence of resistance genes and resistance phenotypes in various in Salmonella strains; however, they also observed that some strains with beta-lactamase resistance genes were still phenotypically susceptible to amoxicillin-clavulanic acid. Therefore, the difference between genotype and phenotype in these strains could be due to exceptional mutations that reduce gene expression and can confer susceptibility to antimicrobial agents used in susceptibility tests.…”
Section: Discussionmentioning
confidence: 96%
“…Twenty-two E. faecalis and E. faecium isolates harboring phenicol-oxazolidinone resistance genes were used as the donor cells, and with Escherichia coli strain J53 served as the recipient strain for the conjugation experiments using methods previously described by Aljahdali et al with minor modifications [ 32 ]. Briefly, each donor and recipient cells were cultured on TSA agar and incubated at 37 °C for 24 h. Cultured donor and recipient cells were mixed in 500 µL LB broth (1:1) and incubated at 37 °C for 3 h. Transconjugants were streaked on LB agar containing 200 mg/L sodium azide and incubated at 37 °C for 24 h. Several colonies were picked and plated on MacConkey agar at 37 °C for 24 h. Transconjugants from MacConkey agar were subcultured on TSA, incubated at 37 °C for 24 h, and subjected to PCR for the optrA , poxtA , cfr , and fexA genes, respectively, according to Table 6 .…”
Section: Methodsmentioning
confidence: 99%